(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to study the general trend of the development of urban area in Latakia Governorate during the period (2001-2022), and to study the economic and social impacts resulting from urban expansion on agricultural lands in the governorate during the mentioned period, where urban expansion was adopted as an independent variable, and the area of agricultural lands, the value Agricultural production and the proportion of agricultural employment as dependent variables. The descriptive analytical approach was used in studying and analyzing the time series of the research variables through tables and arithmetic averages. The standard approach was also used in estimating the general trend equations for the development of urban area, cultivated area, agricultural production, and agricultural employment using the statistical program. (SPSS.20), the results of the research showed a general increasing trend for urban expansion in Latakia Governorate, represented by the area of buildings and public facilities. In contrast, these results showed a general decreasing trend for the area of agricultural land, the value of agricultural production, and the percentage of agricultural labor during the period studied. The results of testing the research hypotheses also showed a negative impact of urban expansion on economic and social activity in Lattakia Governorate. These results showed the existence of a moderate, statistically significant inverse relationship between urban expansion and the area of agricultural land in Lattakia Governorate. The results also showed the presence of a strong, statistically significant inverse relationship between urban expansion. On the one hand, and the value of agricultural production and the proportion of agricultural labor in the governorate on the other hand.